Memori dan amnesia :perbandingan antara anterograde amnesia dan retrograde amnesia - Yusnidah, Md Yunus. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The purpose of this study is to compare between two particular of Amnesia disorder which are Anterograde Amnesia (AA) and Retrograde Amnesia (RA). The preface of this study is to give descriptions on the parts and the regions of the human brain and its function. Human memory is classified into three primary types which are sensory memory, short-term memory and long-term memory. In addition, details descriptions of process long-term potentiation also included. Human memory performs different responsibility to function properly in order to cope with task demand of a person’s everyday life. Thus, there is also downtime for human memory which is known as Amnesia disorder. Generally, Amnesia can be defined as losing a person’s power to remember information, experiences and previous events. Next, symptoms and causes of Amnesia which are Korsakoff disorder, Alzheimer disorder and virus infection such as Herpes Encephalitis would be review. Besides, the lack of treatment and care for Amnesia patient such as effect of Electroconvulsive Theraphy (ECT) and brain surgical would be discussed. Other than that, descriptions of medical drug, and herbal medicine consumption that are suggested to carry out for this disorder would be included. Although, there is no fully recovery of treatment mentioned at least its would help and relief patients.